PENGOLAHAN LIMBAH CAIR SASIRANGAN MELALUI KOMBINASI METODE FILTRASI DAN FITOREMIDIASI SISTEM LAHAN BASAH BUATAN MENGGUNAKAN TUMBUHAN AIR YANG BERBEDA - Untung Santoso; Emmy Sri Mahreda; Fathurrazie Shadiq; Danang Biyatmoko (Universitas Lambung Mangkurat, 2014)
This study aimed to analyze the effect of a combination of filtration methods and fitoremidiasi Constructed wetland systems using different water plants to test the parameters of wastewater treatment sasirangan, analyze the effectiveness and efficiency. The method used is an experimental method. The results showed that the combination of filtration methods and fitoremidiasi artificial wetland systems using different water plants able to improve the quality of effluent sasirangan, where the best result is to use water hyacinth plants (Eichornia crassipes (Mart) Solms) with effectiv level and the highest efficiency for each the parameters include the effective Cr concentration 0.147 mg/L and an efficiency of 29.41%, the concentration of Cd metal with the effectiveness of 0.0981 mg/L and an efficiency of 83.07%, with a BOD concentration of the effectiveness of 101.81 mg/L and an efficiency of 59.84%, the concentration of COD with the effectiveness of 4866.99 mg/L and an efficiency of 91.32%, the effectiveness of the TSS concentration 140.62 mg/L and an efficiency of 60.61%.